Sowing the seeds of peace for food security: Disentangling the nexus between conflict, food security, and peace - Holleman, Cindy; Jackson, Julius; Sánchez, Marco V.; Vos, Rob (Food and Agriculture Organization of the United Nations, 2017)
Why are there still famines and food crises in a world of such affluence? Food crises are complex humanitarian emergencies, but a common factor among them is armed conflict and violence. All 19 countries classified by FAO as being in a state of “protracted (food) crisis” are experiencing conflict and violence. Their predicaments are typically compounded by climatic hazards, such as prolonged droughts, which severely affect food production and livelihoods. Conflict and violence also cause the displacement of millions of people within and between countries, jeopardizing the food security of host communities.